(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examines the role of women self-help project in community development in Central Cross River State, Nigeria. Relevance literature was reviewed and Identity Empowerment theory was adopted for the study. The Survey design was used for the study, and Taro Yamane formula was used to draw respondents. Data collection Method used was the questionnaire. Pearson Product Moment Correlation Coefficients was adopted to analyse the data. Findings from the study indicated among others that, a significant relationship exist between community development and women self-help education projects in central Cross River State. Based on the findings, the following were recommended among others. It is necessary for appropriate legislation to be enacted in all levels of Government to encourage women self-help projects especially in the rural communities, cultural/traditional practices that hinders and restrict women economic and political potentials should be jettisoned, financial credit pool should be created at the local government areas, to be assessed through women Self-help groups.